Effects of Density‐Driven Flows on the Long‐Term Morphodynamic Evolution of Funnel‐Shaped Estuaries. Issue 11 (14th November 2018) - Olabarrieta, Maitane; Geyer, W. Rockwell; Coco, Giovanni; Friedrichs, Carl T.; Cao, Zhendong
Abstract: Subtidal flows driven by density gradients affect the tide‐averaged sediment transport in estuaries and, therefore, can influence their long‐term morphodynamic evolution. The three‐dimensional Coupled Ocean‐Atmosphere‐Wave‐Sediment Transport modeling system is applied to numerically analyze the effects of baroclinicity and Earth's rotation on the long‐term morphodynamic evolution of idealized funnel‐shaped estuaries. The morphodynamic evolution in all the analyzed cases reproduced structures identified in many tide‐dominated estuaries: a meandering region in the fluvial‐tidal transition zone, a tidal maximum area close to the head, and a turbidity maxima region in the brackish zone. As the morphology of the estuaries evolved, the tidal propagation (including its asymmetry), the salinity gradient, and the strength of subtidal flows changed, which reflects the strong bathymetric control of these systems. The comparison with barotropic simulations showed that the three‐dimensional structure of the flow (induced by density gradients) has leading order effects on the morphodynamic evolution. Density gradient‐driven subtidal flows (1) promote near‐bed flood dominance and, consequently, the import of sediment into the estuary, (2) accelerate the morphodynamic evolution of the upper/middle estuary, (3) promote a more concave shape of the upper estuary and reduce the ebb‐tidal delta volume, and (4) produce an asymmetric bathymetry and inhibit the formation of alternate bars that would form under barotropic conditions. This latter effect is the consequence of the combined effect of Earth's rotation and baroclinicity. Key Points: Density‐driven flows affect the long‐term morphodynamic evolution of estuaries by enhancing near‐bed flood dominance The combined effect of baroclinicity and Coriolis acceleration tends to promote cross‐channel bathymetric asymmetry Three‐dimensional process‐based numerical models accounting for salinity variations resemble bathymetric and hydrodynamic features observed in estuaries